2018
DOI: 10.20402/ajbc.2017.0190
|View full text |Cite
|
Sign up to set email alerts
|

Affecting and Satisfaction Factors for Practical Training of Skin Care related College Students

Abstract: Purpose: This study aims to identify career preparation behaviors and career considerations based on career attitude types of cosmetology major college students. Methods: A total of 205 questionnaires were used for the final analysis. Moreover, factor analysis, reliability analysis, cluster analysis, and variance analysis were conducted using the Statistical Package for the Social Sciences (SPSS) program. Results: The career attitude type was sub-categorized into four types: career confidence, career indiffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Whereas, cosmetology careers influence refers to individual's self-knowledge and skills to sustain in their profession [28]. In addition, [26] also affirm that practical training was very helpful in student's prior preparation for work for them to gain knowledge and firm their skills.…”
Section: Results Analysismentioning
confidence: 94%
See 3 more Smart Citations
“…Whereas, cosmetology careers influence refers to individual's self-knowledge and skills to sustain in their profession [28]. In addition, [26] also affirm that practical training was very helpful in student's prior preparation for work for them to gain knowledge and firm their skills.…”
Section: Results Analysismentioning
confidence: 94%
“…Researcher found that previous studies are focus on job performance in beauty industry, cosmetology education and training qualification. There are nine studies focused on Korean cosmetology field [19]; [20]; [21]; [22]; [23]; [24]; [25]; [26]; [27]. Other than that, each study examined Pakistan cosmetology field [12], Midwest cosmetology field [28], Netherlands cosmetology field [11], Turkey cosmetology field [1], Taiwan cosmetology field [29] and Ghana cosmetology field were also included in this review.…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations